2010
DOI: 10.1111/j.1756-185x.2010.01539.x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow lesions in the knee: the clinical conundrum

Abstract: Osteoarthritis (OA) of the knee is a common, debilitating condition. Twelve percent of people aged 60 years or older have symptomatic knee OA. With increasing global incidence of obesity, the prevalence of OA is set to dramatically rise Cartilage deterioration is a hallmark of the disease, but other areas are equally as important, such as changes to the subchondral bone. Magnetic resonance imaging (MRI) has enabled us to view bone marrow lesions (BMLs) in the subchondral bone, allowing progress to be made in u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The spatial association of these changes strongly supports the notion of a close functional relationship between subchondral bone and articular cartilage. This relationship is further highlighted by examining bone marrow lesions (BMLs), discrete abnormalities that can be visualized in the subchondral bone using magnetic resonance imaging (MRI; reviewed in Bassiouni, 90 and Daheshia and Yao 91 ). Although commonly observed in symptomatic OA, 92–95 BMLs are also seen in early (pre-radiographic or asymptomatic) OA.…”
Section: Enhanced Crosstalk Associated With Bmlsmentioning
confidence: 99%
“…The spatial association of these changes strongly supports the notion of a close functional relationship between subchondral bone and articular cartilage. This relationship is further highlighted by examining bone marrow lesions (BMLs), discrete abnormalities that can be visualized in the subchondral bone using magnetic resonance imaging (MRI; reviewed in Bassiouni, 90 and Daheshia and Yao 91 ). Although commonly observed in symptomatic OA, 92–95 BMLs are also seen in early (pre-radiographic or asymptomatic) OA.…”
Section: Enhanced Crosstalk Associated With Bmlsmentioning
confidence: 99%
“…An increased trabecular number, decreased trabecular spacing, and reduced hardness of the bone in OA [ 22 ], due to decreased mineralization [ 23 ], characterize the subchondral bone, especially in zones underlying cartilage degeneration. Discrete zones of subchondral bone that can be imaged using magnetic resonance (MR), termed bone marrow lesions (BML), are frequently observed in both established OA and in early OA, but rarely in symptom free individuals [ 24 , 25 ]. BMLs arise in regions of predicted high loading and contain abnormal bone, with areas of osteocyte death, areas of bone sclerosis with reduced mineral density [ 26 ].…”
Section: Osteoblasts In Oamentioning
confidence: 99%
“…The loss of the articular cartilage changes the stresses on the underlying subchondral bone, which itself has pain receptors. Subchondral bone may react to increasing shearing forces by becoming reactive and sclerotic [23]. Bone scintigraphy studies have shown an increase in delayed phase tracer in the tibiofemoral compartment in of patients reporting knee pain [24].…”
Section: Aetiologymentioning
confidence: 99%